Essential oils: Chemical constituents, potential neuropharmacological effects and aromatherapy - A review - Jiahao Liang; Yuyu Zhang; Penghao Chi; Haonan Liu; Zhaoxuan Jing; Haojie Cao; Yongliang Du; Yutong Zhao; Xia Qin; Wei Zhang; Dezhi Kong (Elsevier, 2023)
Background: Essential oils (EOs) are a plant-derived volatile mixture. Due to their extensive biological activity, EOs have been utilized as ancient remedies to treat a variety of illnesses. Objectives: Our review aims to expand our understanding of EOs' biological activity on the central nervous system (CNS) and to highlight the importance of utilizing EOs in CNS disorders. Method: A systematic literature search was conducted using PubMed, ScienceDirect, China National Knowledge Infrastructure (CNKI), Springer Link, Wan-fang database, and Chinese Biomedicine Database (CBM). The search was conducted to collect relevant journals and contents using the following terms: ''essential oils'', ''aromatherapy'', ''essential oils'' and ''CNS''. Language of publications was unlimited. Results: EOs are concentrated volatile aromatic liquids extracted from natural plants with different chemical compositions, obtained by physical and chemical methods such as distillation and pressing. This paper explores the effects of EOs products on CNS including promoting intelligence, improving sleep, promoting cognition and memory, anti-anxiety and depression, sedation and anti-epilepsy. EOs exert their neuropharmacological effects through blood circulation or the olfactory system. This paper summarizes clinical studies showing that aromatherapy could improve sleep, relieve preoperative anxiety and postoperative PONV, relieve gynecological disease pain, and play a role in hospice care. Conclusion: The present findings suggest that EOs have neuropharmacological effects such as nootropic, sleep improvement, anti-dementia, anti-anxiety and depression, analgesic effect, and antiepileptic, emphasizing the importance of EOs in CNS disorders and indicating the potential clinical application.